The use of material in making gazebo in public area at Presint 14A Putrajaya / Afiq Affandi Abdul Rahman - Abdul Rahman, Afiq Affandi (2014)
This research is done to study the material used in gazebo at Presint 14A Putrajaya. The study looks into type of material used as in gazebo as the findings. The methodologies involved in this research are observation, site and data analysis. The material used for the gazebo depends on the target user and the location of the gazebo. The user will appreciate the safe gazebo, hence the function of gazebo which is the place forgathering area are archieve.